PENGARUH KEMAMPUAN KERJA DAN TINGKAT PENDIDIKAN TERHADAP KINERJA KARYAWAN PADA PT. JAYA ABADI PROSPERO SHOWROOM YAMAHA BULUKUMBA - Anugrah Futri; Agung Widhi Kurniawan; Ilham Wardhana Haeruddin (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to determine the effect of work ability and level of education on employee performance at Pt. Jaya Abadi Prospero Showroom Yamaha Bulukumba. This research is a quantitative research, is a population study. The subjects of this research are employees at PT. Jaya Abadi Prospero Showroom Yamaha Bulukumba with 42 people. Data collection using questionnaires that have been tested for validity and reliability with data analysis carried out using multiple linear regression analysis using two methods, namely simultaneous test (F) and partial test (t) using Statistical Product and Service Solution (SPSS) data processing assistance. The results of this study indicate that: 1) Work ability does not partially affect employee performance based on the partial test results that the work ability variable (X1) on employee performance has a significance value of 0.217 > 0.05 and a t count < t table, namely, 1,255 < 2,023. 2) There is a positive and significant influence between the level of education on employee performance as shown in the results of the t test which has a significance value of 0.000 <0.05 t arithmetic value > t table, namely, 16.296 > 2.023. 3) There is a significant influence between work ability and level of education which together affect employee performance on the results of the simultaneous test with a calculated F value of 132,997 with a probability value (sig) = 0.000. The calculated F value (132.997) > F table (3.23) and sig is less than the probability value of 0.05 or 0.002 < 0.05. With a large influence of 86.6% and the remaining 13.4% influenced by other variables not examined.